Frequency of resistance to Bacillus thuringiensis in field populations of pink bollworm - Tabashnik, Bruce E. (The National Academy of Sciences, 2000)
Strategies for delaying pest resistance to genetically modified crops that produce Bacillus thuringiensis (Bt) toxins are based primarily on theoretical models. One key assumption of such models is that genes conferring resistance are rare. Previous estimates for lepidopteran pests targeted by Bt crops seem to meet this assumption. We report here that the estimated frequency of a recessive allele conferring resistance to Bt toxin Cry1Ac was 0.16 (95% confidence interval = 0.05–0.26) in strains of pink bollworm (Pectinophora gossypiella) derived from 10 Arizona cotton fields during 1997. Unexpectedly, the estimated resistance allele frequency did not increase from 1997 to 1999 and Bt cotton remained extremely effective against pink bollworm. These results demonstrate that the assumptions and predictions of resistance management models must be reexamined.